Pengembangan Website Sistem Penggajian (SIMPEG) Di PDAM Batiwakkal Berau - Sayekti Harits Suryawan; Nindi Dea Adinda; Sandy Erlansyah; Azwar Damari; Muhammad Riyan Adam (Jurnal Suara Pengabdian 45, 2023)
This research aims to develop and modernize the employee payroll administration system at PDAM Batiwakkal Berau through the implementation of the Payroll System Website (SIMPEG). Previously, the process was conducted manually, leading to various challenges in the efficiency and accuracy of payroll data. In addressing these issues, we designed and implemented SIMPEG using the PHP programming language. The results include a significant improvement in the efficiency of the payroll process, minimizing human errors, and ensuring data accuracy. The use of SIMPEG also provides easy access and data management, making it an effective solution for modernizing employee administration at PDAM Batiwakkal Berau. It is expected that the findings of this research will contribute positively to enhancing performance and transparency in employee payroll data management.